MEDIA PEMBELAJARAN INTERAKTIF MENINGKATKAN KETERLIBATAN DAN PEMAHAMAN SISWA DI SEKOLAH SMK PEMBANGUNAN - Rizal Faturrokhman (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The use of interactive learning media in Vocational High Schools (SMK) plays an important role in increasing student engagement and their understanding of the material. These media, such as videos, simulations, and educational games, allow direct interaction with the material. However, implementation at Development Vocational Schools requires a mature strategy to overcome the challenges of technology, resources and teacher training. With training, technology-integrated curriculum development, increased internet access, and external collaboration, the use of interactive learning media can be optimized. Collaboration between stakeholders is the key to success. Through active participation and open communication, interactive learning media can be an eflective solution in improving the quality of education at Development Vocational Schools, preparing students for the digital world of work